2002
DOI: 10.1099/0022-1317-83-12-2933
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 mutants containing the KOS strain ICP34.5 gene in place of the McKrae ICP34.5 gene have McKrae-like spontaneous reactivation but non-McKrae-like virulence

Abstract: Herpes simplex virus type 1 (HSV-1) strain McKrae is neurovirulent in rabbits infected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…However, weight loss, mortality, lesion scores, and neurological scores remained consistent with no significant differences between the genotypes. WT mice with the highly virulent HSV-1 strain McKrae (HSV-1/ McKrae), originally isolated from a patient with ocular herpes (25,26), and monitored them for at least 21 d. Similar to other HSV-1 strains tested, titers of eye swabs from HVEM KO mice were significantly lower than those from WT mice (Fig. 4A).…”
Section: Hsv-2 Causes Severe Disease In Both Wt and Hvem Ko Mice Follmentioning
confidence: 93%
“…However, weight loss, mortality, lesion scores, and neurological scores remained consistent with no significant differences between the genotypes. WT mice with the highly virulent HSV-1 strain McKrae (HSV-1/ McKrae), originally isolated from a patient with ocular herpes (25,26), and monitored them for at least 21 d. Similar to other HSV-1 strains tested, titers of eye swabs from HVEM KO mice were significantly lower than those from WT mice (Fig. 4A).…”
Section: Hsv-2 Causes Severe Disease In Both Wt and Hvem Ko Mice Follmentioning
confidence: 93%
“…The phenotypes produced by HSV-1 infection in mouse models are affected by the strain of virus and mouse as well as the gender and age of the animals (17,27,29,44). Our previous studies have shown that replication of the reporter virus and wild-type strain KOS are essentially identical in cultured Vero cells and outbred CD-1 mice (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the increased virulence of HSV-1 strains such as McKrae correlates with an increased resistance to IFN-␣/␤ (56), it would be of interest to determine if the virulence of HSV-1 strain McKrae maps to the interferon resistance locus of HSV-1 that is formed by the adjacent ICP0 and ICP34.5 genes (20,36,37). Although there are some data to support this hypothesis (42), a rigorous analysis remains to be done.…”
Section: Discussionmentioning
confidence: 99%